Modelo de gestión para promover la cultura organizacional del talento humano con discapacidad del Gobierno Autónomo Descentralizado Municipal del cantón Quevedo, año 2015 - Veliz Jacho, Elena Luzmila (2015)
This research project was developed in Quevedo canton Decentralized Autonomous Government, in Los Ríos province, it is public institution. The objetivo research project is the analysis of the management model to promote organizational culture of human talent Decentralized Autonomous Government Quevedo Canton disability. 2015. For its development was necessary to use the following metodos research such as: allowing tabular statistical information obtained in interviews, presenting them as tables; the cualitativo was applied to organize the data collected, transcribe to text, ie it was collected: documents, records, regulations, internal policies, descriptive data was processed from the words of the people, spoken or written, and behavior observable; the inductivo was applied to obtain the primary information of public servants, so that they know firsthand what the management model used, and how it works organizational culture for staff with disabilities and finally the deductivo was applied to the analysis of interviews conducted fieldwork in the Mayor and Head of Human Resource Management. Of the conclusions reached is that the model of administrative management of GAD Quevedo Canton, is a model of general management, organizational culture responds to competition models, involved in the political structure; have work incentives and economic incentives, but apparently not all share it. The staff provides care to disabled taxpayers who qualify very satisfactory level of care. Whereas the rights and obligations accorded to the human talent with GAD Quevedo Canton disability, adjustments have been made in infrastructure which facilitates access to facilities allowing them to function normally, efficiency and an adequate working environment